Edaravone Enhances Brain-Derived Neurotrophic Factor Production in the Ischemic Mouse Brain - Satoshi Okuyama; Mayu Morita; Atsushi Sawamoto; Tsukasa Terugo; Mitsunari Nakajima; Yoshiko Furukawa (MDPI AG, 2015)
Edaravone, a clinical drug used to treat strokes, protects against neuronal cell death and memory loss in the ischemic brains of animal models through its antioxidant activity. In the present study, we subcutaneously administrated edaravone to mice (3 mg/kg/day) for three days immediately after bilateral common carotid artery occlusion, and revealed through an immunohistochemical analysis that edaravone (1) accelerated increases in the production of brain-derived neurotrophic factor (BDNF) in the hippocampus; (2) increased the number of doublecortin-positive neuronal precursor cells in the dentate gyrus subgranular zone; and (3) suppressed the ischemia-induced inactivation of calcium-calmodulin-dependent protein kinase II in the hippocampus. We also revealed through a Western blotting analysis that edaravone (4) induced the phosphorylation of cAMP response element-binding (CREB), a transcription factor that regulates BDNF gene expression; and (5) induced the phosphorylation of extracellular signal-regulated kinases 1/2, an upstream signal factor of CREB. These results suggest that the neuroprotective effects of edaravone following brain ischemia were mediated not only by the elimination of oxidative stress, but also by the induction of BDNF production.